Management dilemma of cholecysto-colonic fistula: Case report. (2018) - Gibreel, Waleed; Greiten, Lawrence L.; Alsayed, Ahmed; Schiller, Henry J.
Highlights: Cholecystocolonic fistula is different from cholecystoduodenal fistula in that the gallbladder is communicating with the large bowel lumen which has a very high bacterial load. Cholecystocolonic fistula is a two-way communication and this carries a significant risk of biliary sepsis development. Biliary decompression can facilitate cholecystocolonic fistula resolution and healing. Operative intervention in the setting of biliary obstruction after failed decompression should be performed urgently to avoid biliary sepsis. Abstract: Introduction: Cholecystocolonic fistula is a rare condition and is found in roughly 1 in every 10, 000. It represents 6.3% to 26.5% of all cholecystenteric fistulas (Chowbey et al., 2006; Angrisani et al., 2001; Yamashita et al., 1997). Cholecystocolonic fistula is the second most common intestinal fistula after cholecystoduodenal fistula (Costi et al., 2009). Rarity of this condition, atypical presentation, diagnostic and management challenges, makes it a unique surgical entity. Case presentation: A 77-year old male presented with progressive abdominal distension and diarrhea. After initial evaluation, a cholecystocolonic fistula was suspected. Further diagnostic studies including Hepatobiliary Imino-Diacetic Acid (HIDA) scan and Endoscopic Retrograde Cholangiography (ERC) revealed complete occlusion of the cystic duct that could not be relieved. Shortly after, the patient developed septic shock likely of biliary origin and required an urgent open partial cholecystectomy and segmental resection of the involved colonic segment. Discussion: In this particular case, the acute presentation together with the inflammatory features around the gallbladder pointed toward an acute inflammatory process and therefore we have tried to delay any operative intervention to allow the inflammation to subside and avoid operating in an inflamed field. Furthermore, our aim was to relieve any sort of biliary obstruction to allow the fistula −if present- to heal by minimizing bile flow through the fistula. Relieving biliary obstruction was not successful in our patient. Conclusion: Based on our experience with this particular case, we could safely conclude that an operation for cholecystocolonic fistula presence in the setting of biliary obstruction that failed decompressive attempts should be performed in an urgent fashion to avoid biliary sepsis development.